Curated Collections for Educators: Five Key Papers on Evaluating Digital Scholarship - Quinn, Antonia (Cureus, 2018)
Traditionally, scholarship that was recognized for promotion and tenure consisted of clinical research, bench research, and grant funding. Recent trends have allowed for differing approaches to scholarship, including digital publication. As increasing numbers of trainees and faculty turn to online educational resources, it is imperative to critically evaluate these resources. This article summarizes five key papers that address the appraisal of digital scholarship and describes their relevance to junior clinician educators and faculty developers. In May 2017, the Academic Life in Emergency Medicine Faculty Incubator program focused on the topic of digital scholarship, providing and discussing papers relevant to the topic. We augmented this list of papers with further suggestions by guest experts and by an open call via Twitter for other important papers. Through this process, we created a list of 38 papers in total on the topic of evaluating digital scholarship. In order to determine which of these papers best describe how to evaluate digital scholarship, the authorship group assessed the papers using a modified Delphi approach to build consensus. In this paper we present the five most highly rated papers from our process about evaluating digital scholarship. We summarize each paper and discuss its specific relevance to junior faculty members and to faculty developers. These papers provide a framework for assessing the quality of digital scholarship, so that junior faculty can recommend high-quality educational resources to their trainees. These papers help guide educators on how to produce high quality digital scholarship and maximize recognition and credit in respect to receiving promotion and tenure.